2021
DOI: 10.3390/ijerph18031346
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Adolescents’ Sleep: A Longitudinal Study on the Protective Role of Parental Rules Regarding Internet Use before Sleep

Abstract: The popularity of social media use among adolescents has raised concerns about the potentially harmful effects of social media use on adolescents’ sleep. Since longitudinal research considering this relationship is scarce, the present two-wave longitudinal study of 2021 secondary school students (Mage = 13.86, SD = 1.25) examined whether frequency of social media use and problematic social media use predicted adolescents’ bedtime and quality of sleep. Moreover, the protective role of parental rules regarding I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 58 publications
1
30
1
4
Order By: Relevance
“…Such media-specific parenting may thus help adolescents to control their SMU and to prevent social media-related distraction. For instance, parents can set limits to the amount of adolescents’ screentime and restrict adolescents’ phone use at undesired moments, such as at bedtime, while doing homework, while having dinner, or while talking to someone (Shin & Li, 2016 ; van den Eijnden et al, 2021 ). However, parents differ in the extent to which they restrict adolescents’ phone use.…”
Section: Disconnectivity Factors To Explain Heterogeneity In Social M...mentioning
confidence: 99%
“…Such media-specific parenting may thus help adolescents to control their SMU and to prevent social media-related distraction. For instance, parents can set limits to the amount of adolescents’ screentime and restrict adolescents’ phone use at undesired moments, such as at bedtime, while doing homework, while having dinner, or while talking to someone (Shin & Li, 2016 ; van den Eijnden et al, 2021 ). However, parents differ in the extent to which they restrict adolescents’ phone use.…”
Section: Disconnectivity Factors To Explain Heterogeneity In Social M...mentioning
confidence: 99%
“…The current scientific knowledge on the relationship between adolescent media use and well-being is complex, often yielding small effect sizes, conflicting findings and resulting in overall knowledge gaps [3][4][5][6]. Previous research has found positive effects of social media on adolescents, such as an increased level of self-esteem and access to online support networks [7,8], as well as negative effects such as an impaired sleep quality and mental health problems [9,10]. It is important to note that the directionality of these effects is still unclear, in particular for well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of a sufficient number of sleep hours: The need for a sufficient number of sleep hours has already been shown to be of great importance to optimal health and wellbeing [35]. Not getting enough sleep hours may lead to changes in behavior [36] and is associated with attention problems, poor academic performance, daytime fatigue, depression, and obesity [37]. The literature includes many studies that explore the different aspects related to the quality of sleep hours and its connection to technology usage.…”
mentioning
confidence: 99%